(3GdefJbi aj GdCMcGes - (3CMeO Hf YHO GdMdje Hf YHO GdSdGe GdMQGfj, Jbj GdOjf, GHf JjejI, CHh GdYHGS , J (B728 (3g` s
(3ChdgG (B:s
(3jHJOF HHGH HjGf RhGd JWgjQg s
(3BNQgG (B:s
(3ef SQJg MSfJg hSCdJg SjFJg aPdc GdeDef QhGg CMeO hGdJQePi Je GdcJGH hGdMeO ddg hMOg s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B144s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1851s
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdabg GdESdGejs